2015
DOI: 10.1007/s10439-015-1310-y
|View full text |Cite
|
Sign up to set email alerts
|

An Animal-Specific FSI Model of the Abdominal Aorta in Anesthetized Mice

Abstract: Recent research has revealed that angiotensin II-induced abdominal aortic aneurysm in mice can be related to medial ruptures occurring in the vicinity of abdominal side branches.Nevertheless a thorough understanding of the biomechanics near abdominal side branches in mice is lacking. In the current work we present a mouse-specific fluid-structure interaction (FSI) model of the abdominal aorta in ApoE -/-mice that incorporates in vivo stresses. The aortic geometry was based on contrast-enhanced in vivo micro-CT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 42 publications
1
18
1
Order By: Relevance
“…An important simplification of the numerical model was the use of a rigid geometry. In a detailed study of the murine aorta, Trachet et al 35 demonstrate that the inclusion of distensibility resulted in more realistic flow velocity waveforms using fluid structure interactions (FSI) compared to CFD using a rigid geometry. However, CFD and FSI gave similar predictions of WSS at proximal sites near the model inlet 35 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An important simplification of the numerical model was the use of a rigid geometry. In a detailed study of the murine aorta, Trachet et al 35 demonstrate that the inclusion of distensibility resulted in more realistic flow velocity waveforms using fluid structure interactions (FSI) compared to CFD using a rigid geometry. However, CFD and FSI gave similar predictions of WSS at proximal sites near the model inlet 35 .…”
Section: Discussionmentioning
confidence: 99%
“…In a detailed study of the murine aorta, Trachet et al 35 demonstrate that the inclusion of distensibility resulted in more realistic flow velocity waveforms using fluid structure interactions (FSI) compared to CFD using a rigid geometry. However, CFD and FSI gave similar predictions of WSS at proximal sites near the model inlet 35 . Because of this, we reason that the use of a rigid model in our simulations is justifiable because modelling is restricted to the aortic arch which is proximal to the flow inlet.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular modeling and simulation applications are increasingly using image-based fluid-structure interaction modeling to simulate blood flow and blood vessel mechanics ((Taylor and Figueroa 2009), (Kim et al 2009), (Kim et al 2010), (van de Vosse and Stergiopulos 2011), (Tang et al 2011), (Reymond et al 2012), (Xiao et al 2013), (Cuomo et al 2015), (Samyn et al 2015), (Schiavazzi et al 2015), (Trachet et al 2015)). Compared to lumped-parameter models, one- and three-dimensional models that simulate spatially distributed mechanics in vascular networks have the advantage that they more accurately represent the detailed fluid and wall mechanics as well as wave propagation and reflection in arterial networks ((Xiao et al 2013), (Qureshi et al 2014)).…”
Section: Introductionmentioning
confidence: 99%
“…These studies have shown that a FSI method would be most accurate in predicting wall motion in the aneurysm as against only a FEM or a fluid dynamics model [ 75 , 76 ]. This was further demonstrated by Scotti et al, who compared the FEM with a FSI method on 10 aneurysm models.…”
Section: Computational Methods In Aaa Analysismentioning
confidence: 99%